The naturally occurring YMDD mutation among patients chronically infected HBV and untreated with lamivudine: a systematic review and meta-analysis. - Youwen Tan; Keqin Ding; Jing Su; Xuan Trinh; Zhihang Peng; Yuhua Gong; Li Chen; Qian Cui; Na Lei; Xin Chen; Rongbin Yu (PLoS ONE)
Background Several recent reports have demonstrated that tyrosine (Y)-methionine (M)-aspartic acid (D)-aspartic acid (D) (YMDD) motif mutations can naturally occur in chronic HBV patients without antiviral treatment such as lamivudine therapy. This paper aims to assess the overall spontaneous incidence and related risk factors of YMDD-motif mutations among lamivudine-naïve chronic HBV carriers, so as to provide some clue for clinical treatment of hepatitis B. Methodology/principal findings Chinese and English literatures were searched for studies reporting natural YMDD mutations among untreated chronic HBV patients from 2001 to 2010. The incidence estimates were summarized and analyzed by meta-analyses. Forty-seven eligible articles from eight countries were selected in this review (13 in English and 34 in Chinese). The pooled incidence of YMDD-motif mutation among untreated chronic HBV patients from eight countries was 12.21% (95% CI: 9.69%-14.95%). China had an incidence of 13.38% (95% CI: 10.90%-16.07%) and seven other countries had an incidence of 9.90% (95% CI: 3.28%-19.55%), respectively. Lamivudine therapy would increase the risk of mutations 5.23 times higher than the untreated patients. A higher HBV DNA copy number was associated with increased incidence of natural YMDD mutation. No significant difference was found in YMDD mutation incidence between groups of different gender, age, HBeAg status, patients' ALT (alanine aminotransferase) level, and between the groups of HBV genotype B and C. Conclusions The YMDD-motif mutations can occur spontaneously with a relatively high incidence in CHB patients untreated with lamivudine. These mutations might be the consequence of accumulated base mismatch due to the nature of viral polymerase. More fundamental and clinical studies are needed to clarify the influence of YMDD mutations in hepatitis B progression and antiviral treatment.